Faktor Risiko Kejadian Demam Berdarah dengue (DBD) Pada Anak Usia 7-12 Tahun di Kecamatan Samarinda Utara - Elina Erlina; Irfansyah Baharuddin; Yadi Yadi (Universitas Pahlawan Tuanku Tambusai, 2026)
Various factors were suspected to contribute to the occurrence of Dengue Hemorrhagic Fever (DHF); however, the magnitude of each factor's contribution had not been fully determined. This study aimed to analyze factors associated with the incidence of DHF among children aged 7–12 years. An analytical observational study with a case-control design was conducted. The study population consisted of children aged 7–12 years residing in the working areas of Sempaja, Bengkuring, Lempake, and Sungai Siring Community Health Centers. A total of 300 respondents, comprising 150 cases and 150 controls, were selected using Proportionate Stratified Random Sampling. Data were collected using structured questionnaires and observation sheets. Data were analyzed using frequency distribution, Chi-square test, and logistic regression. The results showed that vaccination status, mosquito repellent use, residential density, 3M Plus Mosquito Nest Eradication (PSN 3M Plus) behavior, and socioeconomic status were significantly associated with DHF incidence (p<0.05), whereas sex was not significantly associated (p=0.639). PSN 3M Plus behavior was identified as the strongest factor associated with DHF incidence (OR=22.587). These findings may serve as a basis for strengthening DHF prevention efforts through the control of factors associated with disease occurrence. Keywords: Children Aged 7–12 Years, Dengue Hemorrhagic Fever, Risk Factors